2007
DOI: 10.1002/tox.20275
|View full text |Cite
|
Sign up to set email alerts
|

A new morphospecies of Microcystis sp. forming bloom in the Cheffia dam (Algeria): Seasonal variation of microcystin concentrations in raw water and their removal in a full‐scale treatment plant

Abstract: Toxic cyanobacterial blooms are an increasing problem in Algeria. The production of cyanotoxins (microcystins) and their presence in drinking water represent growing hazards to human health. In this study, seasonal variations in the concentrations of total microcystins and physicochemical parameters (pH, temperature, dissolved oxygen, nitrate, orthophosphate, and chlorophyll-a) were analyzed in the Cheffia dam (Algeria), mainly used to supply drinking water. The removal of cyanobacterial cells and microcystins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…In the surface waters of the northeast Algerian, several studies have shown that cyanobacterial blooms containing microcyst ins were dominated by the genus Microcystic [4,5,6,7,8,9]. Our investigation in the Cheffia dam has shown that this reservoir has seasonal cyanobacterial blooms that start in summer and last into autumn, however Lake Oubeira has persistent blooms that encompass all seasons.…”
Section: Biodiversity Of Toxic Cyanobacteria and Their Toxins In The mentioning
confidence: 62%
See 2 more Smart Citations
“…In the surface waters of the northeast Algerian, several studies have shown that cyanobacterial blooms containing microcyst ins were dominated by the genus Microcystic [4,5,6,7,8,9]. Our investigation in the Cheffia dam has shown that this reservoir has seasonal cyanobacterial blooms that start in summer and last into autumn, however Lake Oubeira has persistent blooms that encompass all seasons.…”
Section: Biodiversity Of Toxic Cyanobacteria and Their Toxins In The mentioning
confidence: 62%
“…Maximum growth rates are attained by most cyanobacteria at temperatures above 25°C. For example, within these two surface waters cyanobacterial blooms have been observed during the warmest months particularly in summer and in early autumn waters [5].…”
Section: Biodiversity Of Toxic Cyanobacteria and Their Toxins In The mentioning
confidence: 95%
See 1 more Smart Citation
“…Three species, Microcystis aeruginosa, M. wesenbergii and M. ichthyoblabe are often found in North African freshwater bodies (Oudra et al 2001, Nasri et al 2004, however, this unusual Microcystis morphospecies was reported for the first time by Nasri et al (2007) as the dominant Microcystis sp. forming bloom in the Cheffia Dam (Algeria).…”
Section: Discussionmentioning
confidence: 99%
“…PAC was successfully used to treat high MC levels in a drinking water treatment process (Nasri, et al, 2007). For effective toxin removal very high doses of PAC are required, and very important parameter is contact time (Chorus, Bartram, 1999;Song, et al, 2005).…”
Section: Activated Carbonmentioning
confidence: 99%